Didyma, Türkei. Der archaische Apollontempel ('Tempel II') in Didyma und die Genese der monumentalen ionischen Sakralarchitektur (Publikationsprojekt). Die Arbeiten der Jahre 2016 und 2017 - Dirschedl, Uta (e-Forschungsberichte des DAI, 2018)
Within the project “The Archaic Apollo temple (‘temple II’) at Didyma” eight hundred architectural and sculptural fragments of the archaic temple and its altar have been documented in both drawings and photographs for the catalogue. The recording was carried out over eleven summer campaigns (2003–2007, 2009–2013, 2017) in the lapidarium of the excavation house at Didyma, and in three campaigns (2005, 2012, 2014/2015) in the magazines and the exhibition rooms of the Antikensammlung Berlin (SMB). The project’s final evaluation and publication under the title “The Archaic Apollo temple (‘temple II’) at Didyma and the genesis of the monumental Ionic sacral architecture” has been funded since February 2016 as an independent research position by the Deutsche Forschungsgemeinschaft (DFG). The book’s submission is scheduled for next year as a habilitation thesis at the faculty of philosophy at the Humboldt-University, Berlin.